PLASMONIC ENHANCEMENT IN MOLECULAR FLUORESCENCE OF NATURAL CURCUMIN DYE WITH SILVER NANOPARTICLES SYNTHESIS & BIOLOGICAL APPLICATION (Journal of Pharmaceutical Negative Results, 2022)
In this study, silver nanoparticles were prepared using the liquid pulse laser ablation technique. To target pure silver immersed in distilled water, a pulsed laser (Nd:YAG) with a wavelength of 1064 nm, number of pulses (600), constant ablation energy (530 mJ) and frequency (1Hz) was used. The effect of adding curcumin at certain concentrations to silver nanoparticles on the optical and structural properties was studied, which included UV spectroscopy, fluorescence spectroscopy, X-ray diffraction (XRD), and electron field emission (FE-SEM) microscop and Fourier transform infrared spectrometry. The (FT-IR) and biological activity of silver nanoparticles and curcumin were tested on two types of bacteria. The results indicated that the increase in curcumin concentration was the reason for the improvement of visual properties. for silver nanoparticles and increase the surface plasmon resonance intensity, thus increasing the formation of nanoparticles, as well as improving the fluorescence. The infrared Fourier test of silver nanoparticles has been studied, as the absorption that appears near wave number (3451) cm-1 is caused by the vibration of the (OH) bond of the alcohol group. The absorption bond (2927) cm-1 is the aromatic (C-H) bond, and this confirms that curcumin acts as a cover agent. An X-ray diffraction study of silver nanoparticles and a hybrid of silver nanoparticles and curcumin was performed. The X-ray diffraction results of silver nanoparticles showed that the crystal system is cubic and polycrystalline, and several angles that are completely identical to the international standard cards for silver were recorded.In this study we studied the biological application on two types of bacteria (E. Coli, Staphylococcus aureus) and the results showed that the highest bacterial inhibition was in the hybrid sample.